Acute multifocal osteomyelitis with septic arthritis caused by nontyphoidal in an immunocompetent young adult: a case report - Boyi Jiang; Hong Xu; Zongke Zhou (Journal of International Medical Research, 2023)
Nontyphoidal Salmonella (NTS) infection can lead to gastroenteritis, enteric fever, and bacteremia. However, bone and joint infections due to NTS are rarely encountered, accounting for only 0.8% of all Salmonella infections and 0.45% of all types of osteomyelitis. We herein report an extremely rare case of acute multifocal osteomyelitis (bilateral femurs and left tibia) with septic arthritis of the bilateral hips caused by Salmonella Dublin in an immunocompetent adult. We performed thorough debridement of the bilateral hips and surgical decompression of the involved bones. At 1 year of follow-up, the patient’s inflammatory biomarkers were within normal limits, and clinical and radiologic examinations showed no signs of infection. We emphasize that invasive NTS can lead to multifocal bone and joint infections in immunocompetent adults. The manifestations of Salmonella osteomyelitis may be insidious; thus, we recommend performing a simultaneous magnetic resonance imaging examination of the bone adjacent to the infected joint to avoid missed or delayed diagnosis. Thorough surgical debridement combined with a long course of sensitive antibiotic therapy is essential to eradicate the infection.